2012
DOI: 10.1074/jbc.m112.421735
|View full text |Cite
|
Sign up to set email alerts
|

Cells Lacking Pfh1, a Fission Yeast Homolog of Mammalian Frataxin Protein, Display Constitutive Activation of the Iron Starvation Response

Abstract: Background: Defects in the protein frataxin give rise to Friedreich ataxia. Results: A new Friedreich ataxia model using fission yeast has been generated and its phenotype and proteome characterized. Conclusion: Frataxin absence triggers a complete iron starvation program, sufficient to generate all the associated respiratory defects. Significance: Our new model system may contribute to decipher the role of frataxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
(66 reference statements)
2
9
0
Order By: Relevance
“…Thus, in S. cerevisiae, low levels of cytosolic iron [65,66], as well as defective mitochondrial ISC biogenesis [67], induce the Aft1p/Aft2p regulatory system, which helps to explain the increase in cellular iron uptake and the redistribution of cytosolic iron to mitochondria in response to frataxin deficiency. It is worth pointing out that Aft1p/Aft2p-dependent activation of the iron regulon in response to frataxin deficiency in S. cerevisiae is analogous to the recently described activation of the iron starvation gene expression programme in S. pombe [40] (discussed above), as well as activation of the cytosolic iron deficiency response in mammalian cells (e.g. up-regulation of TfR1, down-regulation of ferritin and ferroportin 1) [21,25] (discussed above).…”
Section: Figure 2 Alterations In Cardiomyocyte Iron Metabolism In Frdasupporting
confidence: 59%
See 1 more Smart Citation
“…Thus, in S. cerevisiae, low levels of cytosolic iron [65,66], as well as defective mitochondrial ISC biogenesis [67], induce the Aft1p/Aft2p regulatory system, which helps to explain the increase in cellular iron uptake and the redistribution of cytosolic iron to mitochondria in response to frataxin deficiency. It is worth pointing out that Aft1p/Aft2p-dependent activation of the iron regulon in response to frataxin deficiency in S. cerevisiae is analogous to the recently described activation of the iron starvation gene expression programme in S. pombe [40] (discussed above), as well as activation of the cytosolic iron deficiency response in mammalian cells (e.g. up-regulation of TfR1, down-regulation of ferritin and ferroportin 1) [21,25] (discussed above).…”
Section: Figure 2 Alterations In Cardiomyocyte Iron Metabolism In Frdasupporting
confidence: 59%
“…However, mounting evidence indicates that frataxin is likely to play a role in regulating mitochondrial iron metabolism [17,18,36,37]. Further support for a role for frataxin in modulating iron metabolism comes from a recent study in the fission yeast Schizosaccharomyces pombe, in which deletion of the pfh1 gene encoding the frataxin orthologue Pfh1 causes mitochondrial iron overload while simultaneously activating the 'iron starvation' gene expression programme that is regulated in S. pombe by glutaredoxin 4 [40]. Further support for a role for frataxin in modulating iron metabolism comes from a recent study in the fission yeast Schizosaccharomyces pombe, in which deletion of the pfh1 gene encoding the frataxin orthologue Pfh1 causes mitochondrial iron overload while simultaneously activating the 'iron starvation' gene expression programme that is regulated in S. pombe by glutaredoxin 4 [40].…”
Section: Frataxinmentioning
confidence: 99%
“…Most likely, Fe/S cluster binding on Grx4 triggers the release of Php4 from the core subunits of the CCAAT-binding complex. A constitutive repression of Php4 target genes is also seen in cells with defects in the mitochondrial ISC system and in cells depleted for glutathione (Gabrielli et al, 2012;Mercier et al, 2008). Apparently, Php4 senses the fitness of the mitochondrial ISC system through the levels of Fe/S clusters bound to its binding partner Grx4.…”
Section: Cytosolic Glutaredoxins -Fe/s Proteins For Tuning Iron-respomentioning
confidence: 95%
“…Despite these fundamental differences, defects in the mitochondrial ISC systems result in the tuning of these transcription factors in the direction of the response to iron-deprivation in both fungi (Dlouhy and Outten, 2013;Gabrielli et al, 2012;Hausmann et al, 2008;Kaplan and Kaplan, 2009;Philpott et al, 2012). This de-regulation results in the constitutive M a n u s c r i p t 21 activation of cellular iron uptake systems, a massive down-regulation of mRNA transcripts encoding proteins of the mitochondrial respiratory chain and the citric acid cycle, and a transcriptional remodeling of biosynthetic pathways that involve iron-dependent enzymes (Belli et al, 2004;Foury and Talibi, 2001;Hausmann et al, 2008;Ihrig et al, 2010).…”
Section: Iron-responsive Regulators In Fungimentioning
confidence: 99%
“…Iron deprivation can also activate a hypoxia-like signaling in mammals as well as in C. elegans [26,27], and, accordingly, it increased the expression of nhr-57 in an hif-1-dependent manner ( Figure 4A), similar to the above-described effect with frh-1 RNAi or hypoxia (Figures 3G and 3H). We thus speculated that frh-1 RNAi activates the hypoxia-like response through cytosolic iron deprivation, a condition associated with reduced frataxin expression from yeast to mammals as a consequence of progressive mitochondrial iron accumulation [26,39]. Consistent with this possibility, we found that the expression of the C. elegans cytosolic aconitase (aco-1), which is downregulated in response to iron overload like its mammalian homolog iron regulatory protein-1 (IRP1) [40], was significantly increased in frh-1-depleted animals compared to wild-type ( Figure 4B).…”
Section: Frataxin Silencing Induces a Pro-longevity Iron Starvation Rmentioning
confidence: 99%